Implications for the use of ozone (O3) in the adjuvant treatment of COVID-19 (Research, Society and Development, 2020)
Recently, coronavirus disease 2019 (COVID-19) has caused a major global pandemic and poses serious threats to public health. Consequently, there is a worldwide demand to find new treatments to control the new coronavirus pandemic. In the absence of antivirals and vaccines for COVID-19, there is an urgent need to seek therapeutic alternatives capable of mitigating the damage caused by the SARS-CoV-2 virus. Thus, this study seeks, through narrative review, to provide an understanding of the current evidence available regarding the importance of ozone therapy (ozone therapy) and its possible applicability in the treatment of COVID-19. MEDLINE/PubMed, SciELO and LILACS bibliographic databases were used. Evidence shows that ozone (O3) is able to inactivate viruses through direct oxidation of its structural components and block viral replication. Still, due to its modulating action of the inflammatory process, the increase in the cellular and humoral antioxidant and immune system, can attenuate lung diseases and respiratory disorders similar to the complications of the new coronavirus outbreak. Thus, the evidence found in this study indicates that ozone could be proposed as a support for drug therapy in the treatment against viral infections in general and particularly against the new coronavirus (SARS-CoV2), within an integrative medicine approach, justified due to its mechanism of action and the pathogenesis of COVID-19. However, controlled and randomized clinical trials are needed to endorse its effectiveness in preventing, controlling and treating the new coronavirus outbreak.